Solvothermal Synthesis, Characterization and Crystal Structure of Mixed-Valent Complex [Cu(I)(phen)2]·2[Cu(II)(phen)2I]·3I - Chen, Jiong-Ke; Chai, Wen-Xiang; Song, Li; Yang, Yun-Yun; Lin, Jian (Asian Journal of Chemistry, 2012)
The solvothermal reaction of copper(I) iodide and 1,10-phenanthroline (phen) in ethanol solution in presence solution of HI yielded the mixed-valent Cu(I)-Cu(II) compound, namely [Cu(I)(phen)2]·2[Cu(II)(phen)2I]·3I. The crystallzing sample was characterized by elementary analysis. Its structure was determined by single crystal X-ray diffraction experiment. The compound crystallizes in the monoclinic system and adopts a centrosymmetric space group of P21/c, with a = 1.6175(3) nm, b = 1.8659 (4) nm, c = 2.3025 (5) nm, a = 90º, b = 108.708 (2)º, g = 90º, V = 6.582 (2) nm3, Z = 4, Dc = 1.924 g cm-3, F(000) = 3664, μ = 3.36 mm-1. The asymmmetric unit contains one [Cu(I)(phen)2]+ cation, two [Cu(II)(phen)2I]+ cations and three I– anions. Each Cu(I) cation is tetrahedrally coordinated by four nitrogen atoms from two bidentate chelating phen ligands. The coordinate polyhedra of two Cu(II) cations are both trigonal bipyramid, which are composed of four nitrogen atoms from two phen and one iodine atom.